2010
DOI: 10.1021/pr1002593
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography−Mass Spectrometry-Based Parallel Metabolic Profiling of Human and Mouse Model Serum Reveals Putative Biomarkers Associated with the Progression of Nonalcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD), is the most common form of chronic liver disease in most western countries. Current NAFLD diagnosis methods (e.g. liver biopsy analysis or imaging techniques) are poorly suited as tests for such a prevalent condition, from both a clinical and financial point of view. The present work aims to demonstrate the potential utility of serum NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Author Manuscript metabolic profiling in defining phenotypic biomarkers that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 98 publications
5
127
0
Order By: Relevance
“…GNMT deficiency in mice results in chronic hepatitis, fatty liver and HCC spontaneously (25,26,30). Recently, several putative metabolites identified in Gnmt -/-mice serum closely resemble those of NAFLD patients (31). Varela-Rey et al (32) also showed that nicotinamide administration normalized hepatic Sadenosylmethionine (SAM) and fatty acid metabolism, as well as prevented fatty liver development in Gnmt -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…GNMT deficiency in mice results in chronic hepatitis, fatty liver and HCC spontaneously (25,26,30). Recently, several putative metabolites identified in Gnmt -/-mice serum closely resemble those of NAFLD patients (31). Varela-Rey et al (32) also showed that nicotinamide administration normalized hepatic Sadenosylmethionine (SAM) and fatty acid metabolism, as well as prevented fatty liver development in Gnmt -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, FA analysis revealed that the profi les of nonalcoholic fatty liver and NASH are relatively similar, but that NASH and simple steatosis differ in their content of lipoxygenase-derived eicosanoids ( 13,14 ). Lipidomic analyses of human serum indicate that ether-linked phospholipids, certain neutral lipids, and FAs show suggestive differences between NASH and steatosis for some classes of patients by degree of obesity ( 15 ). Ceramides have been proposed to participate in the development and progression of NAFLD ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a manifestation of steatosis, the lipogenesis (triacylglycerols, diacylglycerol, and phospholipids) [51][52][53] and bile acid biosynthesis (cholesterol esters, choline, and bile acids) [54,55] pathways were found to be up-regulated. The hepatic lipids were found to be rearranged and repartitioned from adipose to liver, rather than de novo lipogenesis and deposition in the liver, possibly through increased turnover of phosphatidylcholine and phosphatidylethanolamine [9].…”
Section: Updates In Liver Cancermentioning
confidence: 99%